The influence of media image on brand perception in the digital space of small business - Kasianenko, Karina (Актуальні питання економічних наук, 2025)
In the modern digital economy, the media image has become a critical factor in shaping brand perception, particularly for small businesses operating under budget constraints and high market competition. The growing influence of online platforms in consumer decision-making has led to increased reliance on media communication strategies that prioritize authenticity, emotional engagement, and aesthetic consistency. The relevance of this research lies in the rising need for small enterprises to adapt to these shifts and employ personal and visual media images as strategic tools for survival and growth in the digital marketplace. This article aims to explore the communication mechanism of the media image that shapes brand perception in the minds of digital audiences, focusing on the experiences and limitations of small businesses. Methods: literature analysis ˗ for investigate the current state of research on the topic; generalization and systematization ˗ for the structured, logical, and consistent presentation of research findings. Results. The study revealed that three key components influence the formation of a brand’s media image in the digital space: the quality of visual content, personal representation (particularly by founders or brand ambassadors), and the consistency of the brand narrative across various platforms. The research shows that even without large marketing budgets, small businesses can leverage individual media capital ˗ such as personal presence on social media or collaboration with creative professionals ˗ to create compelling and trustworthy brand images. The analysis of practical cases and interpretive observations confirms that the media image contributes not only to brand recognition and memorability but also to the psychological processes of trust and emotional connection. The results demonstrate that audiences are more likely to engage with and remain loyal to brands that present humanized, coherent, and visually consistent media representations. The research also emphasizes the strategic importance of incorporating video and photo content tailored to platform-specific dynamics, which enhances perceptions of professionalism and credibility. Conclusions. Thus, the media image serves as a cost-effective and highly impactful tool for influencing brand perception in the digital space. Small businesses that successfully integrate media aesthetics, authentic personas, and consistent narrative logic into their branding strategies gain a significant communicative advantage. The article provides both a conceptual and practical foundation for further exploration of media-based branding strategies tailored to resource-constrained market actors.